Thermography in posterior scleritis - A. Kawali; S. Sanjay; P. Mahendradas; R. Shetty (РМЖ "Клиническая офтальмология")
A. Kawali, S. Sanjay, P. Mahendradas, R. Shetty Narayana Nethralaya Eye Hospital, Bangalore, India Aim: to evaluate the utility of thermography in posterior scleritis (PS). Patients and Methods: this prospective observational case-control study included 6 patients with monolateral PS (study group) and 10 healthy volunteers (control group). Ocular surface temperature (OST) was measured in all participants using a non-contact thermal camera (FLIRTM) integrated onto a smartphone (CAT S 60). The difference in OST between the affected eye and the healthy (fellow) eye on thermograms (Δt) was measured at each visit in both groups. Maximum (ΔtMax) and minimum (ΔtMin) Δt for each eye as well as the amplitude of fluctuations (ampΔt) referred to as the difference between ΔtMax and ΔtMin were calculated for each eye. AmpΔt was compared between the groups. Results: in a total of 6 PS patients, B-scan ultrasonography revealed the thickening of the posterior sclera. Choroidal folds (n=4), internal limiting membrane fold (n=2), subretinal fluid (n=3), and optic disc edema (n=2) were identified by eye fundus exam. At presentation, Δt was maximum in all PS patients and reduced unequally after starting treatment. Mean ampΔt was 1.21 °C (1.47–1.04 °C) in PS group and 0.44 °C (0.13–0.63 °C) in the control group. 3 out 6 PS patients were diagnosed with recurrences as demonstrated by OST spikes compared to previous measurements. Conclusion: this article describes a novel technique of the measurement and monitoring of OST. It was demonstrated that PS is associated with the increase in OST measured by thermography. Further large-scale studies are needed to evaluate the potentialities of thermography for detecting occult or subclinical intraocular inflammation. Keywords: ocular thermography, posterior scleritis, ocular surface temperature, eye temperature, occult inflammation. For citation: Kawali A., Sanjay S., Mahendradas P., Shetty R. Thermography in posterior scleritis. Russian Journal of Clinical Ophthalmology. 2020;20(4):204–208. DOI: 10.32364/2311-7729-2020-20-4-204-208.